The effect of e/a ratio on thermodynamic parameters and surface morphology of Cu-Al-Fe-X shape memory alloys - Canbay, Canan Aksu; Aziz, Sivar; Ozkul, Iskender; Dere, Aysegul (Springer, 2020)
In this study, four Cu-Al-Fe-X shape memory alloys were produced by the arc melting technique, and the martensitic transformation temperatures, thermodynamic parameters, and the activation energy values were obtained. The activation energy values of the alloys were calculated as 666.36, 401.6, 82.94, and 226.22 kJ mol(-1) for S1, S2, S3, and S4, respectively. High-temperature phase transitions and eutectoid point of the samples were examined by the differential thermal analysis method. The martensitic diffraction planes of the samples were found as 122, 0022, 1210, and 2012, and the crystallite size of the samples was calculated as 16.21, 20.20, 14.43, and 17.46, respectively. Lastly, optical micrograph observations revealed the morphology of the alloys and the variations in the grains and martensite structures. The e/a ratio of the alloys varied 1.47-1.51, and these values are in agreement with the values in literature to give shape memory effect.
Keywords: e; a ratio; Thermodynamic parameters; Phase transition; Microstructure